Assessing CO2 ${ extCO}_{2}$ Migration Within Faults During Megatonne‐Scale Geologic Carbon Dioxide Storage in Offshore Texas - Lluís Saló‐Salgado; Josimar A. Silva; Lisa Lun; Christie M. Rogers; J. Steven Davis; Ruben Juanes (Water Resources Research)
Abstract Recent studies indicate that Miocene‐age reservoirs offshore Texas are promising candidates for industrial‐scale geologic carbon sequestration. Fault‐bounded hydrocarbon traps are common, and faults may be less competent seals than the low‐permeability sediments overlying the reservoirs; this means that faults may limit the amount of CO2 that can be permanently sequestered. Here, we conduct flow simulations of megatonne‐scale CO2 injection next to a major, reservoir‐bounding growth fault, and evaluate (a) where fault sealing capacity is exceeded, and (b) where the CO2 migrates after it enters the fault zone. We use a geologic model that includes the key structural features of fault‐bounded systems near‐offshore Texas, and consider both homogeneous and layered top seals (TSs). To model fault petrophysics, we apply a new, general methodology for faults in normally‐consolidated, relatively shallow (depth <∼3 km) sequences that populates three‐dimensional realizations of the fault core with sand and clay smears. We quantify uncertainty in the directional components of the fault permeability tensor and multiphase flow fault properties. We evaluate the sensitivity of fault CO2 migration to these properties, and show that the capillary entry pressure is exceeded in the lower portion of the fault. This leads to fault CO2 migration being controlled by effective fault permeability. For the cases considered, the amount of CO2 remaining in the injection formation after 1,000 years exceeds 93%, and CO2 does not migrate to depths shallower than the TS. These results suggest that, in the Miocene section, faults partially offsetting the TS do not act as preferential CO2 conduits.